Selective Expansion of Tregs Using the IL-2 Cytokine Antibody Complex Does Not Reverse Established Alopecia Areata in C3H/HeJ Mice - Lee, Eunjin; Kim, Mingyu; Lee, You Jeong (Frontiers in Immunology, 2022)
Alopecia areata (AA) is an autoimmune disease mediated by NKG2D expressing cytotoxic T lymphocytes destroying hair follicles in the skin. It is one of the most common autoimmune diseases, but there is no effective treatment modality approved by FDA. Regulatory T cells (Tregs) are crucial for suppressing autoreactive T cells, and in the skin, they promote hair growth by inducing anagen. Based on this, we tested the therapeutic potential of expanded Tregs in AA using the C3H/HeJ mice model. In mice with AA, NKG2D expressing CD8 T cells widely infiltrate both in haired and hairless skin area, which have tissue-resident memory T cells phenotype. Tregs in the skin express CD25, CTLA-4, GATA-3, and Jagged-1 and efficiently proliferate by IL-2 cytokine antibody complex. However, expanding Tregs in the skin did not induce anagen in normal mice, indicating they are necessary but not sufficient for anagen induction. Also, they fail to suppress autoreactive CD8 T cells in the skin to reverse established AA in C3H/HeJ mice. These results suggest Treg expansion alone is not sufficient for AA treatment, and combined immunotherapy is required.